Options for Fiscal Consolidation in the United Kingdom - Botman, Dennis (IMF Working Papers; Working Paper ;, 2006)
This paper examines the macroeconomic effects of different timing and composition of fiscal adjustment in the United Kingdom using the IMF's Global Fiscal Model. Early consolidation dampens aggregate demand in the short term, but increases output in the long term as smaller primary surpluses are needed as a result of lower interest payments. Reducing government transfers or current government spending provides larger gains than increasing taxes, in particular compared to raising corporate or personal income taxes. We show that these conclusions are robust under alternative behavioral assumptions and parameterizations. A reduction in global saving would make early consolidation more urgent from both cyclical and long-term perspectives. Finally, we show that tax reform aimed at increasing incentives to save could provide support to fiscal consolidation measures.